Global Budgeting in the OECD Countries - Wolfe, Patrice R. (CENTERS for MEDICARE & MEDICAID SERVICES, 1993)
Many of the Organization for Economic Cooperation and Development countries use global budgeting to control all or certain portions of their health care expenditures. Although the use of global budgets as a cost-containment tool has not been implemented in the United States in any comprehensive way, recent health care reform initiatives have increased the need for research into such tools. In general, the structure, process, and effectiveness of global budgets vary enormously from country to country, in part because the underlying social welfare system of each country is unique.